Evaluasi dan Akuntabilitas dalam Manajemen Pendidikan : Strategi untuk Meningkatkan Kualitas Pembelajaran - Wandi Wandi; Lona Mardiati; Akma Khairun Nisa; Ahmad Sabri; Yusran Lubis (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Educational management plays a strategic role in determining the success of learning processes in various educational institutions. Evaluation and accountability are two interrelated key elements in shaping an effective, transparent, and sustainable education system. This study aims to develop an adaptive and responsive educational management concept to meet contemporary demands and provide strategic recommendations for educational institutions in improving learning quality. Using a qualitative approach with a descriptive-analytical design, this research finds that the integration of systematic evaluation and strong accountability is a fundamental aspect of educational management. Evaluation provides in-depth data on learning effectiveness, while accountability ensures that every component of the educational system takes responsibility for the outcomes achieved. Together, they significantly contribute to creating an educational management mechanism oriented toward continuous quality improvement.